A functional copolymer nylon resin and its preparation method and application
Through the melt condensation polymerization reaction of lactam, comonomer salt, functionalized polysilsesquioxane and ring-opening agent, functional copolymer nylon resin with excellent mechanical properties and flame retardant properties was prepared, and the flame retardant nylon resin was solved. Poor compatibility problems, suitable for a variety of high-performance material applications.
Patent Information
- Application Number
- CN202110698571.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-06-23
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-06-23
AI Technical Summary
The existing nylon resin lacks flame retardancy and poor compatibility with inorganic fillers, which limits its application in electronics, electrical appliances, home appliances and automobiles.
Using lactam, comonomer salt, functionalized polysilsesquioxane and ring-opening agent as reactants, functional copolymer nylon resin is prepared by melt condensation polymerization, forming a functional copolymer nylon resin with excellent mechanical properties, flame retardancy and high compatibility. A functional copolymer nylon resin.
It significantly improves the weather resistance and flame retardant properties of nylon resin and is compatible with inorganic fillers. It is suitable for heat-conducting and heat-sinking components, laser direct molding components and structural devices.
Smart Images

Figure CN115505121B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to polyamide (or nylon) resin, and specifically relates to a functional copolymerized nylon resin and a preparation method and application thereof. Background Art
[0002] Polyamide (PA), commonly known as nylon, is obtained by condensation polymerization of dibasic acid and diamine or amino acid. It is a general term for resins containing repeated amide groups on the molecular chain. As an important raw material for synthetic fibers, synthetic resins and film materials, nylon has excellent comprehensive properties, such as excellent chemical resistance, good wear resistance, high resilience, high breaking strength, good dyeability, good electrical insulation, and good aging resistance. It is also the engineering resin with the largest output, the most varieties, and the widest application among the five major general engineering plastics. It is widely used in automobiles, electronic appliances, transportation, machinery manufacturing, wires and cables, packaging, and daily necessities. However, due to the large number of amide bonds in the molecular structure of nylon, it is very easy to absorb water or moisture, and has disadvantages such as low impact strength, opacity, poor solubility, and poor dimensional stability in dry state or at low temperature, which limits its application. In order to expand the application scope of nylon, existing nylon is usually chemically or physically modified to give it new structure, performance and application field, thereby improving its mechanical strength, surface properties, heat resistance, barrier properties, water absorption and dimensional stability.
[0003] Chemical modification methods include co-condensation polymerization, random copolymerization, block copolymerization, graft copolymerization, and alternating copolymerization. Chinese patent CN106009640A discloses the use of chemical grafting and melt blending to prepare high-barrier graphene oxide / nylon nanocomposites, which utilizes the principle of the reaction between the carboxyl and epoxy groups on the surface of graphene oxide and the amino groups at the end of nylon. Chinese patent CN111087796A reports the preparation of phosphorus-containing nylon by melt exchange reaction of nylon and polyphosphonate under the action of a promoter, thereby improving the flame retardancy and spinnability of nylon. More copolymerization modification work is mainly focused on the copolymerization reaction of lactam monomers and / or aliphatic, alicyclic or aromatic diamines or diacid monomers, and aliphatic, alicyclic or aromatic nylon salts, such as Chinese patents CN108003341A, CN109438976A, CN110092906A (Dongguan Yipuwan), CN109575273A, CN109503828A (Chongqing Shenggan), CN110591082A (Wison China Investment), CN110615892A (Hangzhou Polymer Shun), CN110951073A (Dongchen Ruisen), CN109970970A (Donghua University), CN111635522A (Sichuan University), etc. In general, the copolymerization process includes caprolactam monomer melt and storage; dissolution, storage and concentration of copolymer monomer salt; preparation of additives; high-pressure prepolymerization and multi-step polymerization; casting strip pelletizing; extraction; drying; packaging, etc.
[0004] However, there is no report on the polymerization preparation and process of functional copolymer nylon resin with improved weather resistance and flame retardancy in the prior art. Summary of the invention
[0005] In order to overcome the problems in the prior art that nylon resin itself has no flame retardancy and has poor compatibility with inorganic fillers, the present invention provides a functional copolymer nylon resin, which has excellent mechanical properties, high compatibility with inorganic fillers and flame retardancy, and improved weather resistance. The resin can be used as thermal conductive and heat dissipation components, laser direct forming components and structural devices, and can be used in electronics, electrical appliances, home appliances, automobiles and other fields.
[0006] One of the objects of the present invention is to provide a functional copolymer nylon resin, which comprises reactants of the following components: (1) lactam, (2) comonomer salt, (3) functionalized polysilsesquioxane, and (4) a ring-opening agent; wherein the functionalized polysilsesquioxane is selected from at least one of the compounds represented by formula (I):
[0007]
[0008] In formula (I), at least one (preferably one, two or three) of R2 to R9 is -CH2CH2S-(CH2) n -R1 or -(CH2)n -R1, and the rest are each independently selected from hydrogen, an alkyl group or an aromatic hydrocarbon group; wherein n is an integer greater than or equal to 0, and R1 is selected from the group represented by formula (I-1), -COOH, the group represented by formula (I-2), the group represented by formula (I-3), -OH or -NH2, preferably the group represented by formula (I-1), the group represented by formula (I-2) or the group represented by formula (I-3);
[0009]
[0010] In the present invention, the functionalized polysilsesquioxane used has a reactive site and can react with the copolymerized nylon to form a covalent bond, which makes the copolymerized nylon and the polysilsesquioxane more firmly combined. If a polymer (such as nylon) modified POSS is used, although it contains both an inorganic part and an organic part, it can only be physically mixed with the copolymerized nylon, and the mechanical properties and flame retardancy of the functional copolymerized nylon finally obtained are poorer than those using the functionalized polysilsesquioxane of the present invention.
[0011] In a preferred embodiment, in formula (I), at least one (preferably one, two or three) of R2 to R9 is -CH2CH2S-(CH2) n -R1 or -(CH2) n -R1, the rest are independently selected from hydrogen, C1~C 18 Alkyl or C6~C 24 wherein n is an integer greater than or equal to 1, and R1 is selected from the group represented by formula (I-1) or the group represented by formula (I-2).
[0012] In a further preferred embodiment, in formula (I), at least one (preferably one, two or three) of R2 to R9 is -CH2CH2S-(CH2) n -R1 or -(CH2) n -R1, the rest are independently selected from hydrogen, C1~C 10 Alkyl or C6~C 15 wherein n is an integer from 1 to 10, and R1 is selected from the group represented by formula (I-1) or the group represented by formula (I-2).
[0013] For example, n=1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.
[0014] In a further preferred embodiment, in formula (I), at least one (preferably one, two or three) of R2 to R9 is -CH2CH2S-(CH2) n -R1 or -(CH2) n-R1, and the rest are independently selected from hydrogen, methyl, ethyl, tert-butyl, cycloalkyl or phenyl; wherein n is an integer from 2 to 5 (e.g., 2, 3, 4 or 5), and R1 is selected from the group represented by formula (I-1) or the group represented by formula (I-2).
[0015] Among them, when at least one (preferably one, two or three) of R2 to R9 is -CH2CH2S-(CH2) n -R1 or -(CH2) n -R1 can introduce POSS into the molecular chain of copolyamide, which will affect the crystallization of copolyamide, destroy the crystal structure, and facilitate subsequent processing and modification.
[0016] For example, the functionalized polysilsesquioxane is selected from at least one of the compounds shown in the following formula:
[0017]
[0018]
[0019] In a preferred embodiment, the lactam is selected from at least one of caprolactam, valerolactam and enantholactam.
[0020] In a preferred embodiment, the comonomer salt is selected from at least one of the diamine diacid salts, the diamine is selected from butanediamine, pentanediamine, hexanediamine, heptanediamine, octanediamine, decanediamine, undecanediamine, dodecanediamine, cyclohexyldiamine, p-phenylenediamine, m-phenylenediamine or naphthalenediamine, and the diacid is selected from succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, cyclohexyldicarboxylic acid, undecanediamine, dodecanediamine, terephthalic acid, isophthalic acid or naphthalene diamine.
[0021] In a further preferred embodiment, the comonomer salt is selected from at least one of hexylene diamine adipate, hexylene diamine sebacate, hexylene diamine undecanoate, hexylene diamine dodecanedioate, decanediamine sebacate, decanediamine dodecanedioate, dodecanediamine dodecanedioate, p-phenylenediamine adipate, and m-phenylenediamine adipate.
[0022] In a preferred embodiment, the ring-opening agent is selected from water and / or alkyd acid, and preferably, the water is deionized water.
[0023] In a preferred embodiment, based on the total molar content of lactam and comonomer salt as 100%, the molar content of the lactam is 1-99%, the molar content of the comonomer salt is 1-99%, and the molar content of the functionalized polysilsesquioxane is 0.001-2%.
[0024] In a further preferred embodiment, based on the total molar content of lactam and comonomer salt as 100%, the molar content of the lactam is 20-98%, preferably 40-95%; the molar content of the comonomer salt is 2-80%, preferably 5-60%; and the molar content of the functionalized polysilsesquioxane is 0.01-2%, preferably 0.05-1.5%.
[0025] For example, based on the total molar content of lactam and comonomer salt as 100%, the molar content of lactam is 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 99%, and the molar content of comonomer salt is 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 99%. %, 0.01%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8% or 2%.
[0026] In a preferred embodiment, the weight of the ring-opening agent is 1 to 20 parts, preferably 5 to 15 parts, based on the total weight of the lactam, the comonomer salt and the functionalized polysilsesquioxane being 100 parts.
[0027] For example, based on 100 parts by total weight of the lactam, the comonomer salt and the functionalized polysilsesquioxane, the weight of the ring-opening agent is 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts.
[0028] The role of the ring-opening agent (such as water) is to promote the ring-opening of lactam to carry out copolymerization reaction.
[0029] The polysilsesquioxane of the present invention may be a cage-type polysilsesquioxane or a double-tower polysilsesquioxane, and is not limited to the structure shown in the structural formula.
[0030] The second object of the present invention is to provide a method for preparing the functional copolymer nylon resin described in the first object of the present invention, comprising: reacting raw materials including lactam, comonomer salt, functionalized polysilsesquioxane and a ring-opening agent to obtain the functional copolymer nylon resin.
[0031] In a preferred embodiment, the raw material optionally further comprises an auxiliary agent.
[0032] In a further preferred embodiment, the auxiliary agent is selected from at least one of a heat stabilizer and an antioxidant.
[0033] Among them, the heat stabilizer and antioxidant can be selected from those disclosed in the prior art or commonly used in the art. For example, the heat stabilizer and the antioxidant are selected from one or more of any heat stabilizer and antioxidant disclosed in the prior art, and are not specifically limited here.
[0034] Preferably, the heat stabilizer is selected from at least one of heat stabilizer zinc stearate, heat stabilizer calcium stearate, heat stabilizer barium stearate, heat stabilizer monoglyceride stearate, heat stabilizer trialkyl phosphite, heat stabilizer triaryl phosphite, and heat stabilizer alkyl aryl phosphite, and the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant NDP, antioxidant DLTP, antioxidant TNP, antioxidant TPP, antioxidant MB and antioxidant 264.
[0035] Among them, adding heat stabilizers, antioxidants and other auxiliary agents when synthesizing polymer materials is a common technical means in the art. In the present invention, there is no special limitation on antioxidants and other auxiliary agents, and they can be selected from any one or several disclosed in the prior art. When auxiliary agents are used, the amount of the auxiliary agents can also be within the range known in the prior art.
[0036] In a preferred embodiment, the reaction temperature is 200-300°C, preferably 240-270°C.
[0037] For example, the temperature of the reaction is 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C.
[0038] Among them, it is preferred that the reaction is a melt condensation polymerization reaction.
[0039] In a preferred embodiment, the reaction is carried out in steps under stirring, wherein the stirring speed in the early stage of the reaction is 10-700 rpm, preferably 50-600 rpm, and / or, the stirring speed in the late stage of the reaction is 10-200 rpm, preferably 20-100 rpm; wherein the first 1-7 h, preferably 2-6 h of the reaction is the early stage of the reaction, and the rest is the late stage of the reaction.
[0040] For example, the stirring speed in the early stage of the reaction is 10, 30, 50, 80, 100, 120, 150, 180, 200, 220, 250, 280, 300, 320, 350, 380, 400, 420, 450, 480, 500, 600 or 700 rpm, and the stirring speed in the late stage of the reaction is 10, 30, 50, 80, 100, 120, 150, 180 or 200 rpm; for example, the first 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 6h or 7h of the reaction is the early stage of the reaction, and the period thereafter is the late stage of the reaction.
[0041] In a further preferred embodiment, the stirring speed in the early stage of the reaction is greater than the stirring speed in the late stage of the reaction. Preferably, the stirring speed in the early stage of the reaction is 1 to 70 times (preferably not including 1 time) the stirring speed in the late stage of the reaction.
[0042] For example, the stirring speed in the early stage of the reaction is 1.1, 2, 5, 10, 12, 15, 18, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65 or 70 times the stirring speed in the late stage of the reaction.
[0043] In a preferred embodiment, the preparation method comprises the following steps:
[0044] Step 1, mixing the lactam, the comonomer salt, the functionalized polysilsesquioxane and the ring-opening agent (preferably in a reaction kettle), and maintaining the pressure at 0.1-1 MPa (preferably 0.2-0.5 MPa) under an inert atmosphere;
[0045] For example, maintaining a pressure of 0.1, 0.2, 0.5, 0.8 or 1 MPa under an inert atmosphere;
[0046] Step 2, reacting at the temperature and stirring speed in the early stage of the reaction, maintaining the pressure in the system below 1.5 MPa (preferably, when the pressure in the system exceeds 1.5 MPa, fine-adjusting the pressure relief valve to release the pressure so that the pressure in the system is maintained below 1.5 MPa);
[0047] Step 3, adjusting the stirring speed to the late stage of the reaction, slowly (preferably within 0.5 to 3 hours) releasing the pressure to 0, and then removing impurities and optionally forming to obtain a functional copolymer nylon crude product;
[0048] Step 4: Mix the crude functional copolymer nylon product with water and perform extraction, repeat the extraction step 1 to 6 times, and dry the extracted product to obtain the functional copolymer nylon resin.
[0049] In a preferred embodiment, in step 3, the impurity removal includes vacuuming and / or heating treatment, preferably vacuuming, in order to remove water and unreacted monomers and oligomers.
[0050] In a further preferred embodiment, after the impurity removal in step 3, the material is discharged and optionally molded to obtain the functional copolymer nylon resin; preferably, after the impurity removal in step 3, an inert gas is filled into the system (preferably after stopping vacuuming and turning off stirring), the material is discharged, and then molding is performed.
[0051] The molding may be granulation, spinning, film forming, or any other method suitable for copolymer nylon molding, with granulation being preferred.
[0052] In a preferred embodiment, step 4 is carried out as follows: the functional copolymer nylon crude product and 2 to 5 times its weight of water are introduced into a closed container, extracted at 70 to 110° C. (preferably 90 to 99° C.), and the extraction is cyclically extracted 1 to 6 times (preferably 2 to 5 times), each time for 1 to 5 hours, to obtain the functional copolymer nylon.
[0053] For example, step 4 is carried out as follows: the functional copolymer nylon crude product and 2, 3, 4 or 5 times the weight of water are introduced into a closed container, and extraction is carried out at 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C, and the extraction is cyclically performed 1, 2, 3, 4, 5 or 6 times, each time for 1 hour, 2 hours, 3 hours, 4 hours or 5 hours, to obtain the functional copolymer nylon.
[0054] The third object of the present invention is to provide a functional copolymer nylon obtained by the preparation method described in one of the objects of the present invention, preferably with a viscosity of 1.5 to 4.5.
[0055] For example, the viscosity of the obtained functional copolymer nylon is 1.5, 2, 2.5, 3, 3.5, 4 or 4.5.
[0056] The fourth object of the present invention is to provide the use of the functional copolymer nylon described in the first object of the present invention or the functional copolymer nylon obtained by the preparation method described in the second object of the present invention in thermal conductive and heat dissipation materials, laser direct forming materials, and structural devices.
[0057] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0058] Compared with the prior art, the present invention has the following beneficial effects: in the method described in the present invention, a polymerizable functionalized polysilsesquioxane is introduced in situ into a conventional caprolactam and comonomer salt copolymerization system, and is "embedded" in the copolymerized nylon macromolecular chain by means of end-capping or grafting, thereby giving the copolymerized nylon resin excellent weather resistance and flame retardancy, as well as a high degree of compatibility with inorganic fillers, while maintaining good mechanical properties, thereby achieving better technical effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 The infrared spectrum of the functional copolymer nylon prepared in Example 3 of the present invention is shown. DETAILED DESCRIPTION
[0060] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0061] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0062] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0063] Maleic acid aminopropylene heptaisobutyl polysilsesquioxane, glycidylpropylene heptaethyl polysilsesquioxane, and octaisobutyl polysilsesquioxane were purchased from Hybrid Plastics, Inc., U.S.A. Dicarboxyl double tower type polyhedral oligomeric silsesquioxane is shown in Example 1 of patent CN105198916A, and dihydroxy double tower type polyhedral oligomeric silsesquioxane is shown in Example 7 of patent CN105198916A.
[0064] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0065] Viscosity test: measured by Ubbelohde viscosity method, concentrated sulfuric acid as solvent phase. Tensile performance test: measured according to ISO 527-2 standard using American Instron universal material testing machine, tensile rate 50mm / min. Weather resistance test: measured using Dongguan Ruikai UV accelerated aging box, UV light 340nm, heat flux density 0.68W / m 2 , temperature 60℃, aging time 14 days. Limiting oxygen index test: measured according to GB / T2406 standard using Shanghai Panbiao Qinsun limiting oxygen index instrument. Izod notched impact strength test: measured according to ASTM D256 standard using Italian Ceast pendulum impact instrument. Thermal conductivity: measured according to ASTME1461 standard using German NETZSCH laser thermal conductivity measuring instrument.
[0066] [Example 1]
[0067] In a 10L stainless steel stirred reactor, first add 1468.5g of caprolactam, 628.5g of hexamethylenediamine adipate, 20g of maleic acid aminopropylene heptaisobutyl polysilsesquioxane, and 210g of deionized water, evacuate at room temperature, and blast with high-purity nitrogen for 8 cycles, then blast with high-purity nitrogen again and maintain the pressure at 0.32MPa. Set the polymerization temperature to 264°C, and adjust the stirring speed in the prepolymerization stage to 325rpm; when the pressure in the reactor exceeds 1.5MPa, adjust the speed to 600rpm, and slightly adjust the pressure relief valve to release the pressure to maintain the pressure in the reactor below 1.5MPa. After 5 hours of prepolymerization, the stirring speed was adjusted to 50 rpm, and the post-polymerization reaction was carried out. The pressure was slowly released to 0 within 1.5 hours, and then vacuum dehydration and unreacted monomers and oligomers were carried out. During this period, the reaction temperature was maintained at 264±5°C. After 2 hours, the vacuum was stopped, the stirring was turned off, and high-purity nitrogen was filled. The casting head was heated to 260°C, the feed valve was opened, and the melt strip was extruded and cooled in a water tank before pelletizing. The particles and 5 times the mass of deionized water were introduced into a closed glass container and extracted at 95°C. After 2 hours, the deionized water was poured out, and fresh deionized water was introduced. The extraction was continued, and the cycle was repeated 3 times. Finally, it was dried in a blast oven at 100°C for 24 hours to obtain a functional copolymer nylon resin with a viscosity of 3.07. The analysis and test results are shown in Table 1.
[0068] [Example 2]
[0069] The copolymerization reaction of the functional copolymer nylon resin is the same as that of Example 1, except that the mass of the copolymer monomers is changed to 1050 g of caprolactam and 1047 g of hexamethylenediamine adipate, and a functional copolymer nylon resin with a viscosity of 3.11 is obtained. The analysis and test results are shown in Table 1.
[0070] [Example 3]
[0071] The copolymerization reaction of the functional copolymer nylon resin is the same as that of Example 1, except that the mass of the copolymer monomers is changed to 600.5 g of caprolactam and 1496.5 g of hexamethylenediamine adipate, and a functional copolymer nylon resin with a viscosity of 3.19 is obtained. The analysis and test results are shown in Table 1.
[0072] [Example 4]
[0073] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 1, except that the mass of the copolymerized monomers and the mass of the functionalized polysilsesquioxane are changed: 1440.6 g of caprolactam, 626.4 g of hexamethylenediamine adipate, and 50 g of maleic acid aminopropylene heptaisobutyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 3.15. The analysis and test results are shown in Table 1.
[0074] [Example 5]
[0075] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 1, except that the mass of the copolymerized monomers and the mass of the functionalized polysilsesquioxane are changed: 1419.7 g of caprolactam, 617.3 g of hexamethylenediamine adipate, and 80 g of maleic acid aminopropylene heptaisobutyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 3.09. The analysis and test results are shown in Table 1.
[0076] [Example 6]
[0077] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 1, except that the type and mass of the copolymerized monomers and the mass of the functionalized polysilsesquioxane are changed: 1750 g of caprolactam, 350 g of m-phenylenediamine adipate, and 15 g of maleic acid aminopropylene heptaisobutyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 2.87. The analysis and test results are shown in Table 1.
[0078] [Example 7]
[0079] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 1, except that the type and mass of the copolymerized monomers and the mass of the functionalized polysilsesquioxane are changed: 1750 g of caprolactam, 250 g of hexamethylenediamine sebacate, 100 g of m-phenylenediamine adipate, and 15 g of maleic acid aminopropylene heptaisobutyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 2.79. The analysis and test results are shown in Table 1.
[0080] [Example 8]
[0081] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 1, except that the type and mass of the copolymerized monomers and the mass of the functionalized polysilsesquioxane are changed: 1750 g of caprolactam, 350 g of p-phenylenediamine adipate, and 15 g of maleic acid aminopropylene heptaisobutyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 3.01. The analysis and test results are shown in Table 1.
[0082] [Comparative Example 1]
[0083] When the functionalized polysilsesquioxane is not added, the copolymerization reaction of the copolymerized nylon resin is the same as in Example 1, except that the type and mass of the copolymerized monomers are changed and the functionalized polysilsesquioxane is not added: 1482.5 g of caprolactam and 634.5 g of hexamethylenediamine adipate, to obtain a copolymerized nylon resin with a viscosity of 3.22. The analysis and test results are shown in Table 1.
[0084] [Comparative Example 2]
[0085] The copolymerization reaction of the copolymerized nylon resin was the same as that in Example 1, except that an equal molar amount of octaisobutyl polysilsesquioxane was used to replace the maleic acid aminopropylidene heptaisobutyl polysilsesquioxane. The analysis and test results are shown in Table 1.
[0086] Table 1:
[0087]
[0088] As can be seen from Table 1, compared with Comparative Example 1, the functional copolymerized nylon resin prepared in Examples 1 to 3 and Examples 4 to 5 has the advantages of higher mechanical strength / modulus retention rate and flame retardant properties after UV aging as the functionalized polysilsesquioxane variables are regulated. The use of aromatic nylon salts in Examples 6 to 8 is beneficial to improving the mechanical strength and performance of copolymerized nylon. In general, the weather resistance of the functional copolymerized nylon resin in the present invention is significantly improved, and it shows excellent flame retardant properties.
[0089] [Example 9]
[0090] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 1, except that the type and mass of the copolymerized monomers and the type and mass of the functionalized polysilsesquioxane are changed: 1750 g of caprolactam, 350 g of m-phenylenediamine adipate, and 15 g of glycidylpropylene heptaethyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 2.76. The analysis and test results are shown in Table 2.
[0091] [Example 10]
[0092] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 9, except that the type and mass of the copolymerized monomers and the type and mass of the functionalized polysilsesquioxane are changed: 1500 g of caprolactam, 600 g of m-xylylenediamine adipate, and 15 g of glycidylpropyleneheptaethylpolysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 2.80. The analysis and test results are shown in Table 2.
[0093] [Example 11]
[0094] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 9, except that the type and mass of the copolymerized monomers and the type and mass of the functionalized polysilsesquioxane are changed: 1200 g of caprolactam, 900 g of m-xylylenediamine adipate, and 15 g of glycidylpropyleneheptaethylpolysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 2.80. The analysis and test results are shown in Table 2.
[0095] [Example 12]
[0096] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 9, except that the type and mass of the copolymerized monomers and the type and mass of the functionalized polysilsesquioxane are changed: 1500 g of caprolactam, 300 g of m-phenylenediamine adipate, 300 g of p-phenylenediamine adipate, and 15 g of glycidylpropylene heptaethyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 2.71. The analysis and test results are shown in Table 2.
[0097] [Example 13]
[0098] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 9, except that the type and mass of the copolymerized monomers and the type and mass of the functionalized polysilsesquioxane are changed: 1200 g of caprolactam, 300 g of m-phenylenediamine adipate, 600 g of p-phenylenediamine adipate, and 15 g of glycidylpropylene heptaethyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 2.68. The analysis and test results are shown in Table 2.
[0099] [Example 14]
[0100] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 9, except that the type and mass of the copolymerized monomers and the type and mass of the functionalized polysilsesquioxane are changed: 1465 g of caprolactam, 300 g of m-phenylenediamine sebacate, 300 g of hexamethylenediamine azelate, and 50 g of glycidylpropylene heptaethyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 2.79. The analysis and test results are shown in Table 2.
[0101] [Example 15]
[0102] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 9, except that the type and mass of the copolymerized monomers and the type and mass of the functionalized polysilsesquioxane are changed: 1200 g of caprolactam, 265 g of enantholactam, 300 g of m-phenylenediamine sebacate, 300 g of hexamethylenediamine azelate, and 50 g of glycidylpropylene heptaethyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 2.67. The analysis and test results are shown in Table 2.
[0103] [Example 16]
[0104] The copolymerization reaction of the functional copolymerized nylon resin is the same as that of Example 9, except that the type and mass of the copolymerized monomers and the type and mass of the functionalized polysilsesquioxane are changed: 1200 g of caprolactam, 240 g of enantholactam, 300 g of m-phenylenediamine adipate, 300 g of p-phenylenediamine dodecanoate, and 75 g of glycidylpropylene heptaethyl polysilsesquioxane, to obtain a functional copolymerized nylon resin with a viscosity of 2.67. The analysis and test results are shown in Table 2.
[0105] [Comparative Example 3]
[0106] When the functionalized polysilsesquioxane is not added, the copolymerization reaction of the copolymerized nylon resin is the same as that of Example 9, except that the type and mass of the copolymerized monomers are changed and the functionalized polysilsesquioxane is not added: 1762.5 g of caprolactam and 352.5 g of m-xylylenediamine adipate, to obtain a copolymerized nylon resin with a viscosity of 2.98. The analysis and test results are shown in Table 2.
[0107] Table 2:
[0108]
[0109] [Example 17]
[0110] Preparation of laser direct structuring materials:
[0111] After drying, 60 parts of the functional copolymer nylon in Example 1 were mixed with 35 parts of chopped glass fibers (diameter 13 μm, length 3 mm), 7 parts of copper chrome black, 0.5 parts of white oil, and 0.5 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] at room temperature. Then, the mixture was introduced into the main feeding port of a LABTECH co-rotating twin-screw extruder (screw diameter 16 mm, aspect ratio 40), and melt-kneaded and extruded at 275°C, 220 rpm, and a feed rate of 5 kg / h, cooled, and granulated to obtain a laser direct molding nylon material. Its properties are shown in Table 3.
[0112] Laser Activation:
[0113] The surface of the nylon alloy injection molding profile was activated by HAIYI LASER fiber laser, with a laser output power of 20 watts, a laser wavelength of 1064 nanometers, a laser speed of 2500 mm / s, and a pulse frequency of 40 kHz to obtain a laser etched circuit.
[0114] Chemical copper plating:
[0115] The surface of the injection molded profile after laser activation was purged with compressed air and cleaned with ultrasonic waves, and chemical copper plating was performed using the MacDermelus chemical plating process for 1.5 hours.
[0116] [Comparative Example 4]
[0117] The preparation, laser activation and chemical copper plating of the nylon alloy material are the same as those in Example 17, except that the copolymerized nylon in Comparative Example 1 is used as the base material. The properties are shown in Table 3.
[0118] Compared with Comparative Example 4, Example 17 in Table 3 shows that the mechanical strength and toughness of the nylon alloy material prepared by using the functional copolymer nylon are higher than those of the common copolymer nylon system, showing excellent composite compatibility. This indicates that the functionalized polysilsesquioxane component in the functional copolymer nylon is beneficial to improving the interface performance between the organic resin and the inorganic material, and plays an in-situ strengthening and toughening effect.
[0119] Table 3:
[0120] source Tensile strength MPa Tensile modulus MPa Impact strength J / m Embodiment 17 89 5455 106 Comparative Example 4 85 5400 98
[0121] [Example 18]
[0122] Preparation of thermal conductive and heat dissipation materials:
[0123] After drying, 75 parts of the functional copolymer nylon in Example 9 were mixed with 4 parts of graphite (average particle size 80 μm), 20 parts of spherical alumina (average particle size 10 μm), 0.5 parts of white oil, and 0.5 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] at room temperature. Then, the mixture was introduced into the main feeding port of a LABTECH co-rotating twin-screw extruder (screw diameter 16 mm, aspect ratio 40), and melt-kneaded and extruded at 275°C, 220 rpm, and a feed rate of 5 kg / h, cooled, and granulated to obtain a thermal conductive nylon material. Its properties are shown in Table 4.
[0124] [Comparative Example 5]
[0125] The preparation of the thermal conductive and heat dissipating material is the same as that of Example 18, except that the copolymerized nylon resin in Comparative Example 2 is used as the base material. The properties thereof are shown in Table 4.
[0126] [Comparative Example 6]
[0127] The thermal conductivity of the copolymerized nylon in Comparative Example 2 was directly tested. Its performance is shown in Table 4.
[0128] Table 4:
[0129]
[0130] Compared with Comparative Examples 5 and 6, Example 18 in Table 4 shows that the thermal conductive nylon material prepared using functional copolymer nylon has significantly better thermal conductivity than the ordinary copolymer nylon system, indicating that the introduced polysilsesquioxane component plays an auxiliary role in the thermal diffusion of the system and shows better heat dissipation performance.
[0131] [Example 19]
[0132] In a 10L stainless steel stirred reactor, first add 1750g of caprolactam, 350g of m-phenylenediamine adipate, 15g of dicarboxyl double tower type polyhedral oligomeric silsesquioxane, and 210g of deionized water, evacuate at room temperature, and blast with high-purity nitrogen for 8 cycles, then blast with high-purity nitrogen again and maintain the pressure at 0.32MPa. Set the polymerization temperature to 264°C, and adjust the stirring speed in the prepolymerization stage to 325rpm; when the pressure in the reactor exceeds 1.5MPa, adjust the speed to 600rpm, and slightly adjust the pressure relief valve to release the pressure to maintain the pressure in the reactor below 1.5MPa. After 5 hours of prepolymerization, the stirring speed was adjusted to 50 rpm, and the post-polymerization reaction was carried out. The pressure was slowly released to 0 within 1.5 hours, and then vacuum dehydration and unreacted monomers and oligomers were carried out. During this period, the reaction temperature was maintained at 264±5°C. After 2 hours, the vacuum was stopped, the stirring was turned off, and high-purity nitrogen was filled. The casting head was heated to 260°C, the feed valve was opened, and the melt strip was extruded and cooled in a water tank before pelletizing. The particles and 5 times the mass of deionized water were introduced into a closed glass container and extracted at 95°C. After 2 hours, the deionized water was poured out, and fresh deionized water was introduced. The extraction was continued, and the cycle was repeated 3 times. Finally, it was dried in a blast oven at 100°C for 24 hours to obtain a functional copolymer nylon resin with a viscosity of 2.70. The analysis and test results are shown in Table 5.
[0133] [Example 20]
[0134] In a 10L stainless steel stirred reactor, first add 1050g of caprolactam, 1047g of hexamethylenediamine adipate, 20g of dihydroxy double tower type polyhedral oligomeric silsesquioxane, and 210g of deionized water, evacuate at room temperature, and blast with high-purity nitrogen for 8 cycles, then blast with high-purity nitrogen again and maintain the pressure at 0.32MPa. Set the polymerization temperature to 264°C, and adjust the stirring speed in the prepolymerization stage to 325rpm; when the pressure in the reactor exceeds 1.5MPa, adjust the speed to 600rpm, and slightly adjust the pressure relief valve to release the pressure to maintain the pressure in the reactor below 1.5MPa. After 5 hours of prepolymerization, the stirring speed was adjusted to 50 rpm, and the post-polymerization reaction was carried out. The pressure was slowly released to 0 within 1.5 hours, and then vacuum dehydration and unreacted monomers and oligomers were carried out. During this period, the reaction temperature was maintained at 264±5°C. After 2 hours, the vacuum was stopped, the stirring was turned off, and high-purity nitrogen was filled. The casting head was heated to 260°C, the feed valve was opened, and the melt strip was extruded and cooled in a water tank before pelletizing. The particles and 5 times the mass of deionized water were introduced into a closed glass container and extracted at 95°C. After 2 hours, the deionized water was poured out, and fresh deionized water was introduced. The extraction was continued, and the cycle was repeated 3 times. Finally, it was dried in a blast oven at 100°C for 24 hours to obtain a functional copolymer nylon resin with a viscosity of 3.00. The analysis and test results are shown in Table 5.
[0135] Table 5:
[0136]
[0137] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A functional copolymer nylon resin comprising reactants of the following components: (1) lactam, (2) comonomer salt, (3) functionalized polysilsesquioxane, and (4) a ring-opening agent; wherein: The functionalized polysilsesquioxane is selected from at least one of the compounds represented by formula (I): Formula (I); In formula (I), two of R2 to R9 are -CH2CH2S-(CH2) n -COOH or -CH2CH2S-(CH2) n -OH, the rest are independently selected from hydrogen, C1~C 18 Alkyl or C6~C 24 or, one of R2 to R9 is -(CH2) n -R1, the rest are independently selected from hydrogen, C1~C 18 Alkyl or C6~C 24 wherein n is an integer greater than or equal to 1, and R1 is selected from the group represented by formula (I-1) or the group represented by formula (I-2); ; The lactam is selected from at least one of caprolactam, valerolactam and enantholactam; The comonomer salt is selected from at least one of hexylene diamine adipate, hexylene diamine sebacate, hexylene diamine undecanoate, hexylene diamine dodecanedioate, decanediamine sebacate, decanediamine dodecanedioate, dodecanediamine dodecanedioate, p-phenylenediamine adipate, and m-phenylenediamine adipate; Taking the total molar content of lactam and comonomer salt as 100%, the molar content of lactam is 40-95%, the molar content of comonomer salt is 5-60%, and the molar content of functionalized polysilsesquioxane is 0.01-2%.
2. The functional copolymer nylon resin according to claim 1, characterized in that In formula (I), two of R2 to R9 are -CH2CH2S-(CH2) n -COOH or -CH2CH2S-(CH2) n -OH, the rest are independently selected from hydrogen, C1~C 10 Alkyl or C6~C 15 or, one of R2 to R9 is -(CH2) n -R1, the rest are independently selected from hydrogen, C1~C 10 Alkyl or C6~C 15 wherein n is an integer of 1 to 10, and R1 is selected from the group represented by formula (I-1) or the group represented by formula (I-2).
3. The functional copolymer nylon resin according to claim 1, characterized in that: The ring-opening agent is selected from water and / or alkyd.
4. The functional copolymer nylon resin according to claim 1, characterized in that: The weight of the ring-opening agent is 1 to 20 parts based on the total weight of the lactam, the comonomer salt and the functionalized polysilsesquioxane as 100 parts.
5. The functional copolymer nylon resin according to claim 1, characterized in that: The weight of the ring-opening agent is 5 to 15 parts based on the total weight of the lactam, the comonomer salt and the functionalized polysilsesquioxane as 100 parts.
6. The method for preparing the functional copolymer nylon resin according to any one of claims 1 to 5, comprising: Raw materials including lactam, comonomer salt, functionalized polysilsesquioxane and ring-opening agent are reacted to obtain the functional copolymer nylon resin.
7. The preparation method according to claim 6, characterized in that: The raw material optionally further comprises an auxiliary agent.
8. The preparation method according to claim 7, characterized in that: The auxiliary agent is selected from at least one of a heat stabilizer and an antioxidant.
9. The preparation method according to claim 6, characterized in that: The reaction temperature is 200-300°C; and / or, The reaction is carried out step by step under stirring, wherein the stirring speed is 10-700 rpm in the early stage of the reaction, and the stirring speed is 10-200 rpm in the late stage of the reaction; wherein the first 1-7 hours of the reaction is the early stage of the reaction, and the rest is the late stage of the reaction.
10. The preparation method according to any one of claims 6 to 9, characterized in that: The preparation method comprises the following steps: Step 1, mixing the lactam, the comonomer salt, the functionalized polysilsesquioxane and the ring-opening agent, and maintaining the pressure at 0.1-1 MPa under an inert atmosphere; Step 2, reacting at the reaction temperature and stirring speed in the early stage of the reaction, maintaining the pressure in the system below 1.5 MPa; Step 3, adjusting the stirring speed to the late stage of the reaction, slowly releasing the pressure to 0, and then removing impurities and optionally forming to obtain a functional copolymer nylon crude product; Step 4: Mix the crude functional copolymer nylon product with water, perform extraction, cycle the extraction for 1 to 6 times, and dry the extracted product to obtain the functional copolymer nylon resin.
11. The preparation method according to claim 10, characterized in that: In step 3, the impurity removal includes vacuuming and / or heating treatment; and / or, After the impurity removal in step 3, discharge and optionally form the material to obtain the functional copolymer nylon resin; and / or, Step 4 is carried out as follows: the functional copolymer nylon crude product and 2 to 5 times the weight of water are introduced into a closed container, extracted at 70 to 110° C., and cyclically extracted 1 to 6 times, each time for 1 to 5 hours, to obtain the functional copolymer nylon.
12. The functional copolymer nylon obtained by the preparation method according to any one of claims 6 to 11.
13. The functional copolymer nylon according to claim 12, characterized in that: Its viscosity is 1.5~4.
5.
14. Use of the functional copolymer nylon according to any one of claims 1 to 5 or the functional copolymer nylon obtained by the preparation method according to any one of claims 6 to 11 in thermal conductive and heat dissipation materials, laser direct forming materials, and structural devices.
Citation Information
Patent Citations
Preparation method of graphene oxide and polyamide nanocomposite material with high barrier property
CN106009640A
High-temperature-resistant low-water-absorption copolymerized nylon and preparation method thereof
CN108003341A
Copolymerized nylon product and preparation method thereof
CN109438976A
Semi-aromatic long carbon chain copolymer nylon and synthesis method thereof
CN109503828A
High-temperature-resistant semi-aromatic copolymerization nylon and method for preparing same
CN109575273A
Cited By
Reactive phosphorus-nitrogen flame retardant as well as preparation method and application thereof
CN116693788A